Sunlight-Driven Synthesis of Silver Nanoparticles Using Pomelo Peel Extract and Antibacterial Testing - Vinh Tien Nguyen (Journal of Chemistry)
A green approach, including using phytochemicals in pomelo peel extract (PPE) and direct sunlight, was used to synthesize silver nanoparticles (AgNPs). PPE was prepared by treating pomelo peel with a citric acid solution at 85°C for 2 h. PPE was then mixed with AgNO3 and exposed to sunlight to induce the formation of AgNPs. Time-dependent UV-vis spectra of the reaction mixture demonstrated that AgNPs are formed under sunlight irradiation faster than underheating at 90°C. Characterization techniques, including X-ray diffraction, transmission electron microscopy, and scanning electron microscopy, confirmed the formation of AgNPs with sizes of 20–30 nm. AgNPs synthesized in PPE were more stable toward electrolyte-induced aggregation than those synthesized using the conventional NaBH4/citrate method. The AgNPs synthesized in PPE showed antibacterial activities comparable to those of AgNO3 at the same silver concentration against four pathogenic bacterial strains. The obtained PPE containing AgNPs, pectin, and other phytochemicals can be utilized further to produce antibacterial and antioxidant films in food packaging and medical applications.